A Preliminary Study on Developing Vocational-based Public Speaking Learning Materials for Business Communication - Apriyanti, Difiani; Djonnaidi, Silvia; Izzatul Laili, Hamidah; Anggraini, Rina; Erdian, Sabriandi; Adzkia, Aisyah Syahadatul (UIR Press, 2025)
The business world requires its employees to have public speaking skills as one of communication strategies. The skills are used for negotiating, collaborating, and networking with national and international parties that leads to global development. As business world relies on Polytechnics’ graduates, lecturers must equip students with public speaking skills specifically for business communication. This study investigates students' perception on public speaking for business communication, which later on will be the based of developing learning materials. Questionnaires consisting of three aspects, namely needs, wants, and lack were given to 48 students enrolled in the Public Speaking of Business Communication course in English Department of Politeknik Negeri Padang. The data from the instruments were then analyzed descriptively. The results show that the students have not fully understood the concept of writing the business script, delivering the public speaking in business environment, and the relation with business communication. The conclusion generated from this research is vocational higher institutions like polytechnics must start to introduce the essential of public speaking in business environment by providing suitable materials.